2019
DOI: 10.1029/2018gl081612
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Northward Propagation of Boreal Summer Intraseasonal Oscillation Revealed by Climate Model Experiments

Abstract: Northward propagation of the boreal summer intraseasonal oscillation (ISO) has profound impacts on Northern Hemisphere extreme weather events. This study aims to test the hypotheses proposed in the previous studies to explain northward propagation of the ISO by drastically changing the climatological mean states through lowering the Tibetan Plateau (TP) with a fully coupled Earth system model, Nanjing University of Information Science and Technology Earth System Model version 3.0. The model reproduces realisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Previous studies focusing on northward propagation of BSISO convection in the eastern IO have suggested that vorticity anomalies by zonal vertical shear may be the dominant factor for northward propagation of ISO (DeMott et al, 2013; Yang, Wang, & Lee, 2019). We speculate that because much warmer SST and more abundant moisture occur in the WNP compared to those in the eastern IO, convection may be mainly generated due to upward transport of moisture by surface fluxes processes rather than dynamical processes in the WNP.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies focusing on northward propagation of BSISO convection in the eastern IO have suggested that vorticity anomalies by zonal vertical shear may be the dominant factor for northward propagation of ISO (DeMott et al, 2013; Yang, Wang, & Lee, 2019). We speculate that because much warmer SST and more abundant moisture occur in the WNP compared to those in the eastern IO, convection may be mainly generated due to upward transport of moisture by surface fluxes processes rather than dynamical processes in the WNP.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…To obtain the effect of different mean state on BSISO northward propagation, we conduct three experiments: (1) the NESM3.0 with observed orography (TP100); (2) orography reduced by 50% (TP50); and (3) flat orography (TP00) over the TP region (60–110°E, 25–45°N). Figure 1 of Yang, Wang, and Lee (2019) shows a horizontal map of orography over the TP region used in the experiments. We smooth the boundaries of the orographic area based on the method of Cannon et al (2017) to remove undesired numerical noises.…”
Section: The Model and Diagnostic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several mechanisms have been advanced to explain the NP of BSISO (Wang and Xie 1996;Xie and Wang 1996;Jiang et al 2004;Bellon and Sobel 2008;Zheng and Huang 2019). Jiang et al (2004) proposed the vertical wind shear mechanism for the NP of BSISO, which was further confirmed with numerical simulation studies (Drbohlav and Wang 2005;Yang et al 2019). Under a background state flow with easterly vertical wind shear, the combination of vertical shear flow and meridional gradient of baroclinic divergence could lead to positive barotropic vorticity in the free atmosphere to the north of convection center.…”
Section: Introductionmentioning
confidence: 73%